Acute Visual Disorders—What Should the Neurologist Know? - Brune, Anthony J.; Gold, Daniel R. (Seminars in Neurology, 2019)
Normal vision requires coordination of precisely controlled and coordinated eye movements and normal function of a large cortical and subcortical sensory network. Given the required precision of the system and wide anatomic distribution of the motor and sensory visual systems, vision can be disrupted by a variety of central and peripheral nervous system disorders. While many of these may be relatively benign or have no proven therapy, several may be isolated presentations or harbingers of more serious neurologic conditions. Both monocular and binocular vision losses may be isolated presentations of stroke or its equivalent. Other etiologies of monocular vision loss may represent the initial presentation of potentially disabling conditions. Binocular diplopia, caused by impaired movement of one or both eyes, may represent a condition with no acute therapy and a benign natural history, or a progressive potentially life-threatening syndrome. Most people are heavily reliant upon vision, so that even a subtle change in vision due to disturbed afferent or efferent pathways is invariably noticed, and presentation to the emergency department for eye symptoms is common. The accurate evaluation of these patients in the acute setting is essential to identify the patients requiring immediate testing or treatment.
Keywords: diplopia; vision loss; optic neuritis; giant cell arteritis